2017
DOI: 10.1103/physrevc.96.041302
|View full text |Cite
|
Sign up to set email alerts
|

Dipole and quadrupole moments of Cu7378 as a test of the robustness of the Z=28 shell closure near et al.

Abstract: Nuclear spins and precise values of the magnetic dipole and electric quadrupole moments of the ground states of neutron-rich 73-78 Cu isotopes were measured using the Collinear Resonance Ionization Spectroscopy (CRIS) experiment at the CERN On-Line Isotope Mass Separator (ISOLDE) facility. The nuclear moments of the less exotic 73,75 Cu isotopes were remeasured with similar precision, yielding values that are consistent with earlier measurements. The moments of the odd-odd isotopes, and 78 29 Cu (N = 49) in pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…It illustrates that in 73m Zn a certain degree of proton excitations across the closed Z = 28 shell and neutron excitations across the N = 50 shell gaps are important. This was also observed recently in the neutron-rich Cu isotopes via mass and moment measurements [17,36]. The most noteworthy conclusion from Fig.…”
Section: A Tracking the Source Of Collectivitysupporting
confidence: 60%
See 2 more Smart Citations
“…It illustrates that in 73m Zn a certain degree of proton excitations across the closed Z = 28 shell and neutron excitations across the N = 50 shell gaps are important. This was also observed recently in the neutron-rich Cu isotopes via mass and moment measurements [17,36]. The most noteworthy conclusion from Fig.…”
Section: A Tracking the Source Of Collectivitysupporting
confidence: 60%
“…Measurements of ground state properties from laser spectroscopy have also provided considerable nuclear structure information in this region [14][15][16][17][18][19]. With one proton above Z = 28, a study of Cu isotopes revealed a primarily single-particle nature and a weak "magic" behavior around N = 40 from the spins, moments, and charge radii, but also showed a nonnegligible contribution from NN correlations and cross-shell excitations [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time the production of copper isotopes 75−79 Cu at the CERN-ISOLDE facility supports the doubly magic character of 78 Ni [4]. The magnetic dipole and the electric quadrupole moments of 78 29 Cu and other Cu isotopes, measured using the CRIS experiment at the CERN-ISOLDE facility suggests that the magicity of Z = 28 and N = 50 is restored towards 78 Ni [5].…”
Section: Introductionmentioning
confidence: 67%
“…Precision laser spectroscopy can simultaneously measure multiple nuclear properties of isotopes in a nuclear modelindependent way, such as nuclear spins, electromagnetic moments, and changes in the mean-square charge radii. This makes such measurements a major ingredient for nuclear structure studies in different regions of the nuclear chart, providing important benchmarks for testing and developing state-of-the-art nuclear theories [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%